THE PRACTICE OF BUYING AND SELLING FOOD THROUGH THE JUANGJEK APPLICATION IN BIREUEN CITY VIEWED FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Ichsan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to find out how the practice of buying and selling food through the JuangJek Application in Bireuen City is viewed from an Islamic economic perspective. This research uses a descriptive qualitative method where the legal basis used to find out the practice of buying and selling food through the JuangJek Application is based on the istishna contract. The data source used in the primary data. Data collection techniques are carried out using observation, interviews, and documentation techniques where then the data will be analyzed using data collection techniques, data reduction, and data presentation. Based on the data analysis that has been carried out, the results are obtained that the practice of buying and selling food through the JuangJek Application in the istishna contract is appropriate and considered legal. This is because there are three aspects used, namely the payment aspect, the terms of the goods, and the agreement. Where these three aspects have met and are in accordance with the provisions of DSN-MUI Fatwa No. 6 of 2000.